2013
DOI: 10.1061/(asce)ir.1943-4774.0000635
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Design of Alternate and Conventional Furrow Fertigation to Minimize Nitrate Loss

Abstract: Alternate furrow fertigation has shown potential to improve water and fertilizer application efficiency in irrigated areas. The combination of simulation and optimization approaches permits to identify optimum design and management practices in furrow fertigation, resulting in optimum cost, irrigation performance or environmental impact. The objective of this paper is to apply 1D surface and 2D subsurface simulation-optimization models to the minimization of nitrate losses in two types of alternate furrow fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…For this reason, Xu et al (2013) proposed a two-dimensional coupled model for simulating surface water and solute transfer in basin fertigation. Ebrahimian et al (2013b) presented a 1D surface and 2D subsurface simulation-optimization model to minimize nitrate losses in two types of alternate furrow fertigation (variable and fixed alternate furrow irrigation) and in conventional furrow irrigation. The model used numerical surface fertigation (Abbasi et al, 2003c) and soil water (SWMS-2D) models to simulate water flow and nitrate transport in the soil surface and subsurface, respectively.…”
Section: Developed Surface Fertigation Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, Xu et al (2013) proposed a two-dimensional coupled model for simulating surface water and solute transfer in basin fertigation. Ebrahimian et al (2013b) presented a 1D surface and 2D subsurface simulation-optimization model to minimize nitrate losses in two types of alternate furrow fertigation (variable and fixed alternate furrow irrigation) and in conventional furrow irrigation. The model used numerical surface fertigation (Abbasi et al, 2003c) and soil water (SWMS-2D) models to simulate water flow and nitrate transport in the soil surface and subsurface, respectively.…”
Section: Developed Surface Fertigation Modelsmentioning
confidence: 99%
“…For instance, if an irrigation event shows high percolation losses, fertilizer injection early in the irrigation time will lead to relevant fertilizer leaching (Jaynes et al, 1992 sely, if the irrigation event shows large runoff losses, injecting fertilizer late in the irrigation time will lead to large runoff losses (Ebrahimian et al, 2013b). Key questions in recommending fertigation practices include when, how much and what kind of fertilizer to apply in surface irrigation water.…”
Section: Fertigation Recommendations: Key Management Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies that evaluated fertigation timing in furrow irrigation (e.g., Bouwer et al 1990;Playán and Faci 1997;Sabillón and Merkley 2004;Adamsen et al 2005;Burguete et al 2009;Ebrahimian et al 2013b). For example, Bouwer et al (1990) and Soroush et al (2012) recommended that in order to avoid leaching of fertilizers to groundwater, fertigation should be applied toward the end of an irrigation event.…”
Section: Introductionmentioning
confidence: 99%
“…Burguete et al (2009) developed a simulation model, which considered overland water flow, solute transport and infiltration, and used it to evaluate the effects of irrigation discharge, fertilizer application timing and furrow geometry on fertilizer uniformity. Ebrahimian et al (2013b) used genetic algorithms and the one-dimensional surface and two-dimensional subsurface models to optimize timing of fertigation in alternate furrow irrigation. They concluded that by optimizing the start time and the duration of fertilizer injection, they could reduce nitrate losses due to deep percolation and surface runoff by up to 50 %.…”
Section: Introductionmentioning
confidence: 99%